Napoleon Bonaparte: His Successes and Failures - Sultana, Zakia (European Journal of Multidisciplinary Studies, 2017)
Napoleon Bonaparte (1769-1821), also known as Napoleon I, was a French military leader and emperor who conquered much of Europe in the early 19th century. Born on the island of Corsica, Napoleon rapidly rose through the ranks of the military during the French Revolution (1789-1799). After seizing political power in France in a 1799 coup d’état, he crowned himself emperor in 1804. Shrewd, ambitious and a skilled military strategist, Napoleon successfully waged war against various coalitions of European nations and expanded his empire. However, after a disastrous French invasion of Russia in 1812, Napoleon abdicated the throne two years later and was exiled to the island of Elba. In 1815, he briefly returned to power in his Hundred Days campaign. After a crushing defeat at the Battle of Waterloo, he abdicated once again and was exiled to the remote island of Saint Helena, where he died at 51.Napoleon was responsible for spreading the values of the French Revolution to other countries, especially in legal reform and the abolition of serfdom. After the fall of Napoleon, not only was the Napoleonic Code retained by conquered countries including the Netherlands, Belgium, parts of Italy and Germany, but has been used as the basis of certain parts of law outside Europe including the Dominican Republic, the US state of Louisiana and the Canadian province of Quebec. The memory of Napoleon in Poland is favorable, for his support for independence and opposition to Russia, his legal code, the abolition of serfdom, and the introduction of modern middle class bureaucracies. The social structure of France changed little under the First Empire. It remained roughly what the Revolution had made it: a great mass of peasants comprising three-fourths of the population—about half of them works owners of their farms or sharecroppers and the other half with too little land for their own subsistence and hiring themselves out as laborers. Industry, stimulated by the war and the blockade of English goods, made remarkable progress in northern and eastern France, whence exports could be sent to central Europe; but it declined in the south and west because of the closing of the Mediterranean and the Atlantic. The great migrations from rural areas toward industry in the towns began only after 1815. The nobility would probably have declined more swiftly if Napoleon had not restored it, but it could never recover its former privileges. Finally we can say that many of the territories occupied by Napoleon during his Empire began to feel a new sense of nationalism.